Identification of the PTPN22 functional variant R620W as susceptibility genetic factor for giant cell arteritis. Issue 11 (14th August 2013) - Serrano, A; Márquez, A; Mackie, S L; Carmona, F D; Solans, R; Miranda-Filloy, J A; Hernández-Rodríguez, J; Cid, M C; Castañeda, S; Morado, IC; Narváez, J; Blanco, R; et al.
Abstract : Objective: To analyse the role of the PTPN22 and CSK genes, previously associated with autoimmunity, in the predisposition and clinical phenotypes of giant cell arteritis (GCA). Methods: Our study population was composed of 911 patients diagnosed with biopsy-proven GCA and 8136 unaffected controls from a Spanish discovery cohort and three additional independent replication cohorts from Germany, Norway and the UK. Two functional PTPN22 polymorphisms (rs2476601/R620W and rs33996649/R263Q) and two variants of the CSK gene (rs1378942 and rs34933034) were genotyped using predesigned TaqMan assays. Results: The analysis of the discovery cohort provided evidence of association of PTPN22 rs2476601/R620W with GCA (PFDR =1.06E-04, OR=1.62, CI 95% 1.29 to 2.04). The association did not appear to follow a specific GCA subphenotype. No statistically significant differences between allele frequencies for the other PTPN22 and CSK genetic variants were evident either in the case/control or in stratified case analysis. To confirm the detected PTPN22 association, three replication cohorts were genotyped, and a consistent association between the PTPN22 rs2476601/R620W variant and GCA was evident in the overall meta-analysis (PMH =2.00E-06, OR=1.51, CI 95% 1.28 to 1.79). Conclusions: Our results suggest that the PTPN22 polymorphism rs2476601/R620W plays an important role in the genetic risk to GCA.